Zinc biofortified rice varieties: Challenges, possibilities, and progress in India - Sanjeeva Rao, D.; Neeraja, C. N.; Madhu Babu, P.; Nirmala, B.; Surman, K.; Subba Rao, L. V.; Surekha, K.; Raghu, P.; Longvah, T.; Surendra, P.; Kumar, Rajesh; Ravindra Babu, V.; et al. (Frontiers Media, 2020)
Zinc malnutrition is a major issue in developing countries where polished rice is a staple food. With the existing significant genetic variability for high zinc in polished rice, the development of biofortified rice varieties was targeted in India with support from HarvestPlus, Department of Biotechnology, and Indian Council of Agricultural Research of Government of India. Indian Institute of Rice Research (IIRR) facilitates rice varietal release through All India Coordinated Rice Improvement Project (AICRIP) and also supports rice biofortification program in India. Various germplasm sets of several national institutions were characterized at IIRR for their zinc content in brown rice using energy-dispersive X-ray fluorescence spectroscopy indicating the range of zinc to be 7.3 to 52.7 mg/kg. Evaluation of different mapping populations involving wild germplasm, landraces, and varieties for their zinc content showed the feasibility of favorable recombination of high zinc content and yield. Ninety-nine genotypes from germplasm and 344 lines from mapping populations showed zinc content of ≥28 mg/kg in polished rice meeting the target zinc content set by HarvestPlus. Through AICRIP biofortification trial constituted since 2013, 170 test entries were nominated by various national institutions until 2017, and four biofortified rice varieties were released. Only the test entry with target zinc content, yield, and quality parameters is promoted to the next year; thus, each test entry is evaluated for 3 years across 17 to 27 locations for their performance. Multilocation studies of two mapping populations and AICRIP biofortification trials indicated the zinc content to be highly influenced by environment. The bioavailability of a released biofortified rice variety, viz., DRR Dhan 45 was found to twice that of control IR64. The technology efficacy of the four released varieties developed through conventional breeding ranged from 48 to 75% with zinc intake of 38 to be 47% and 46 to 57% of the RDA for male and female, respectively. The observations from the characterization of germplasm and mapping populations for zinc content and development of national evaluation system for the release of biofortified rice varieties have been discussed in the context of the five criteria set by biofortification program.